Analisis Koordinasi Antar Pihak pada Proyek Konstruksi Bangunan Gedung Melalui Studi Literatur - Laras Alencia Eka Putri; Tri Kuncoro; Mei Fajri Anugrah Sukma; Retno Dwi Rahmawati (Universitas Batanghari Jambi, 2026)
Building construction projects involve various parties with different roles, responsibilities, and interests, requiring effective coordination to achieve the established time, cost, and quality targets. The complexity of building construction projects demands the integration of various activities, resources, and decision-making processes among the parties involved. Lack of coordination can lead to various issues such as work delays, communication errors, conflicts between parties, and discrepancies between project outcomes and planning. This research aims to analyze coordination among parties in building construction projects through a literature study approach. The research method used is a literature study with a descriptive qualitative approach through the stages of problem identification, literature search, literature selection, content analysis, and synthesis of research results based on relevant national and international scientific articles. The research results show that the effectiveness of coordination is influenced by factors such as communication, information exchange, stakeholder involvement, decision-making, and information management systems. Coordination obstacles found include delayed information, lack of communication, unclear task distribution, and differing objectives among parties. This study recommends the implementation of regular coordination meetings, increased stakeholder involvement, and the application of an integrated information system to enhance the effectiveness of building construction project coordination.